2015
DOI: 10.1007/s10495-015-1161-x
|View full text |Cite
|
Sign up to set email alerts
|

An epistatic effect of apaf-1 and caspase-9 on chlamydial infection

Abstract: Chlamydia is an obligate intracellular bacterial pathogen that replicates solely within a membrane-bound vacuole termed an inclusion. Chlamydia seems to perturb multiple cellular processes of the host, such as, rearrangement of the membrane trafficking system for its intracellular multiplication, and inhibition of host cell apoptosis for persistent infection. In an attempt to clarify host factor involvement in apoptosis regulation, we found that inhibition of Caspase-9 restricted, while Apaf-1 promoted, Chlamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…3a). This supports the previous observation that caspase-9 accumulates in inclusions (Rahman et al, 2015), as well as the finding of the Y2H assay. Further investigation is required to clarify the EB factor(s) involved in the binding of caspase-9 and its significance.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…3a). This supports the previous observation that caspase-9 accumulates in inclusions (Rahman et al, 2015), as well as the finding of the Y2H assay. Further investigation is required to clarify the EB factor(s) involved in the binding of caspase-9 and its significance.…”
supporting
confidence: 92%
“…In our previous study, we found that during C. pneumoniae infection, caspase-9 was sequestered to, and accumulated into, the inclusion and, interestingly, it was activated even under conditions lacking Apaf-1, and caspase-9 activation supported infection by C. pneumoniae (Rahman et al, 2015). It is possible that there might be many paths involved in the control of host apoptosis by chlamydial infection and each Chlamydia species evolutionally alter different paths for their tissue or host tropism.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The Bcl2 family of proteins plays a central role in the apoptosis process. The Bcl2 family includes Bcl2, Bax, Bad, and Bcl-xL (Zheng et al, 2016;Rahman et al, 2015 JPET # 265082 20 inhibit apoptosis. In fact, the ratio of Bax to Bcl2 determines the sensitivity to cell death (Amin et al, 2014).…”
Section: Drg Tissues and The Sciatic Nervementioning
confidence: 99%